If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -33 = 3(u + 3) + 3u Reorder the terms: -33 = 3(3 + u) + 3u -33 = (3 * 3 + u * 3) + 3u -33 = (9 + 3u) + 3u Combine like terms: 3u + 3u = 6u -33 = 9 + 6u Solving -33 = 9 + 6u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-6u' to each side of the equation. -33 + -6u = 9 + 6u + -6u Combine like terms: 6u + -6u = 0 -33 + -6u = 9 + 0 -33 + -6u = 9 Add '33' to each side of the equation. -33 + 33 + -6u = 9 + 33 Combine like terms: -33 + 33 = 0 0 + -6u = 9 + 33 -6u = 9 + 33 Combine like terms: 9 + 33 = 42 -6u = 42 Divide each side by '-6'. u = -7 Simplifying u = -7
| 15-5x+15+2+1=2x-2+10+2 | | 3x^2+1x+6=0 | | -15+n=-0 | | 23y+90+4(10.25-0.125y)+4=180 | | X+15=25+12 | | -3(x+5)-3x=5-(2+x)+7 | | 142=7+3(-7x+3) | | g-1.6=2.8 | | .8*X=24 | | 14+12v=-16+9 | | 20-43=3(x-1)-5 | | 0=6x+13 | | j-3.79=14.21 | | 21y-1=4x+23+9x-38 | | y=6(0)+13 | | 80*X=24 | | x+2x+(x+3)=75 | | 11b-12=-10 | | f+6=8 | | 6(5)-1=5(5-1)-3(7-2(1)) | | 5=q+2 | | 9(0)-7y=14 | | 10x-3=20+15 | | -8n+5(4n+8)=100 | | 2x-5x+3x-25+5x+45=180 | | -3p-6(5-2p)=4(p-2)-47 | | .1x+10=.35x | | -2=w^7 | | 5x+7=2.5(2x+2.8) | | 9x-7(0)=14 | | 6(5)=5(5-1)-3(7-2(1)) | | f-8=11 |